Deciphering Pain and Pruritus in Keloids from the Perspective of Neurological Dysfunction: Where Are We Now? - En Yang; Ruoqing Xu; Hanrui Zhang; Wenzheng Xia; Xin Huang; Tao Zan (Biomedicines)
Keloids are a typical skin fibroproliferative disease that can cause severe aesthetic and functional concerns. Pain and pruritus are the most common clinical symptoms of keloids, but the mechanisms underlying these symptoms remain unclear. The peripheral nervous system plays a pivotal role in the transmission of superficial sensation signals. Mounting evidence has shown potential correlations between disturbance in the peripheral nervous system and pain and pruritus in keloids. Here, we summarize the role of neurological dysfunction in the development of pain and pruritus, with a specific focus on neuroanatomical alterations, the dysfunction of sensory nerves, and neurogenic inflammation.